Emotional Intelligence and Empathy among Ophthalmologists - Muhammad Shaheer; Asima Rafique; Zahid Kamal Siddiqui (Shalamar Medical & Dental College, Lahore, Pakistan, 2023)
Background: Emotional intelligence and empathy plays a key role in coping with varying situations in daily life. Objective: The purpose of this study was to determine emotional intelligence and empathy among ophthalmologists. Methods: This cross-sectional study was carried out at the College of Ophthalmology & Allied Vision Sciences from 1st June 2022 till 31st December 2022. After the ethical approval of the study, a Google form was developed which included Schutte's scale (Emotional Intelligence) and Davis's Interpersonal index (Empathy) questions in addition to those related to basic demographic information. A sample size of 19 was calculated and sampling was done by non-probability convenient sampling. The proforma was sent via social media application (WhatsApp) to study participants. A total of 39 ophthalmologists including residents and faculty members of either gender responded to be part of the study. A comparison of emotional intelligencescores was done by applying Independent sample t-test and one-way ANOVA. Results: A total of 39 ophthalmologists participated in the study with a mean age of 35.31 ± 9.83 years. The Emotional Appraisal‖ mean score was found to be highest in post-graduate residents (p = 0.05) and the mean scores of the sub-scale -Non-Verbal Communication‖ was highest in faculty (Assistant professor or above in designation) followed by Postgraduate resident (PGR), (p=0.04). Comparison of empathy scores revealed asignificant difference in the sub-scales of the Davis scale -Perspective taking‖ (p = 0.04) and Personal distress (p=0.03) between the male and female participants. Conclusion: Among ophthalmologists, postgraduate residents were better in terms of emotional intelligence than faculty who had better skills with regards to non-verbal communication.